RELIGIOUS CHARACTER-BASED LEARNING STRATEGY AT MTS AL-QODIRI I JEMBER - Nur Laili (IAI Darussalam, 2020)
This study aims to explain the organization of learning, delivery of learning and management of religious character-based learning in Al-Qur'an Hadith subjects at MTs Al-Qodiri 1 Jember. The research method uses a qualitative approach. The results of the research are: 1) the organization of learning based on religious characters has been mapped out, which classes are considered as capable students, which students are less capable, and which students really need the attention of a teacher. Before the lesson begins the teacher invites to pray together, and do apperception. For classes that are able, then immediately carry out learning by starting to read the Qur'an together; 2) delivery of religious character-based learning using various media. While the method used in learning is adapted to the material. Before using the method, the teacher first asks the students about the method that will be used in the learning; and 3) the management of religious character-based learning is scheduled and each teacher has a record of student progress. The notes are in the form of values ??and in the form of attitudes. The score is obtained from a written test or an oral exam. In order for students to get satisfactory grades, the teacher always motivates the students.